2006
DOI: 10.1093/eurheartj/ehl382
|View full text |Cite
|
Sign up to set email alerts
|

The long-term cost-effectiveness of cardiac resynchronization therapy with or without an implantable cardioverter-defibrillator

Abstract: Long-term treatment with CRT-P appears cost-effective compared with MT alone. From a life-time perspective, assuming a reasonable life expectancy when receiving effective treatment for heart failure, CRT-ICD may also be considered cost-effective when compared with CRT-P + MT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
158
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(170 citation statements)
references
References 19 publications
8
158
2
2
Order By: Relevance
“…[16][17][18] The reduction in hospitalizations and hospitalization days with CRT therapy observed in RAFT would be anticipated to result in substantial healthcare savings, but the magnitude of this benefit awaits the completion of a detailed cost-effectiveness analysis. [16][17][18] Given that hospital stay may vary dramatically by geographic region, we examined the duration of hospital stay for HF by geographic region: Australia, Canada, Europe, and Turkey. 19 The average length of stay was similar between regions.…”
Section: Crt and Hospitalizations For Hfmentioning
confidence: 99%
“…[16][17][18] The reduction in hospitalizations and hospitalization days with CRT therapy observed in RAFT would be anticipated to result in substantial healthcare savings, but the magnitude of this benefit awaits the completion of a detailed cost-effectiveness analysis. [16][17][18] Given that hospital stay may vary dramatically by geographic region, we examined the duration of hospital stay for HF by geographic region: Australia, Canada, Europe, and Turkey. 19 The average length of stay was similar between regions.…”
Section: Crt and Hospitalizations For Hfmentioning
confidence: 99%
“…Analyses of controlled trials have shown the time dependency of the beneficial effects of ICDs on mortality, with a lack of benefit in the first months after implantation and an exponential rise in benefit thereafter reaching a peak after 3 years [65]. Accordingly, economic analyses have shown that it may need up to 6-7 years of follow-up to be cost effective [66,67]. Thus, ICDs may not be indicated in patients with ACHF and a predicted short life expectancy.…”
Section: Implantable Cardioverter Defibrillator (Icd)mentioning
confidence: 99%
“…Only the COMPANION trial has directly compared the relative effectiveness of CRT‐D versus CRT‐P; it found lower risk of cardiac death for CRT‐D versus CRT‐P, but the trial was powered to compare each device to medical therapy alone, not to compare the 2 devices 12. CRT‐D devices are nearly 3 times more costly and require more frequent battery replacements compared with CRT‐P13; accordingly, cost‐effectiveness analyses have suggested that the incremental benefit of CRT‐D over CRT‐P may not justify the large cost difference 14, 15…”
mentioning
confidence: 99%